Comparison of Bond Strength Between Three Types of Denture Teeth and the Acrylic Resin of a Complete Removable Denture Base - Khalilzadeh, Shohreh; Etesami , Soroush (Galen Medical Journal, 2024)
Introduction: To prepare a denture, the patient, dentist, and technician spend considerable time and money. The most common denture repair is the replacement and repair of detached teeth in a prosthesis. This study aimed to compare the bond strength between three different types of artificial teeth and a heat-cured acrylic denture base. Materials and Methods: In this in vitro experimental study, the shear bond strength of three groups of artificial teeth, including Apple & Glamor composite and B-Star nanocomposite, to a heat-cured acrylic resin denture base was compared. 10 samples were selected from each group. Samples were attached to the heat-cured resin. For bond strength assessment, the samples were placed in a universal testing machine and subjected to shear force at 1 mm/min speed, and the fracture load was recorded. Using SPSS 23 software and descriptive statistics, the mean force of fracture and the standard deviation of samples were calculated. One-way ANOVA and Tukey tests were used to compare the shear bond strength of the samples. Results: the mean shear bond strength of Apple composite teeth was recorded at 336 N. Also, for Glamor composite and B-Star nanocomposite denture teeth, the mean shear bond strength were recorded at 246 N and 154 N, respectively. Conclusion: The highest shear bond strength belong to Apple composite teeth and then to Glamor composite and B-Star nanocomposite denture teeth, respectively.